2011
DOI: 10.1007/s00270-011-0228-5
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Embolization versus Myomectomy: Impact on Quality of Life—Results of the FUME (Fibroids of the Uterus: Myomectomy versus Embolization) Trial

Abstract: UAE and myomectomy both result in significant and equal improvements in QoL. UAE allows a shorter hospital stay and fewer major complications but with a higher rate of reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 36 publications
8
115
0
10
Order By: Relevance
“…Several randomised controlled trials have described major complications in up to 15 % of patients following UAE (Pinto et al 2003;Mara et al 2006;Volkers et al 2006;Manyonda et al 2011;Dutton et al 2007;Edwards et al 2007) and smaller observational studies have also reported higher complication rates of 11-26 % (Razavi et al 2003;Goodwin et al 2006;Siskin et al 2006). On the other hand, the most recently published prospective randomised trial (FUME) reported a much lower major complication rate of 2.9 % (Manyonda et al 2011). A summary of complication rates from various reports are outlined in Table 2.…”
Section: Overall Complication Ratesmentioning
confidence: 91%
See 1 more Smart Citation
“…Several randomised controlled trials have described major complications in up to 15 % of patients following UAE (Pinto et al 2003;Mara et al 2006;Volkers et al 2006;Manyonda et al 2011;Dutton et al 2007;Edwards et al 2007) and smaller observational studies have also reported higher complication rates of 11-26 % (Razavi et al 2003;Goodwin et al 2006;Siskin et al 2006). On the other hand, the most recently published prospective randomised trial (FUME) reported a much lower major complication rate of 2.9 % (Manyonda et al 2011). A summary of complication rates from various reports are outlined in Table 2.…”
Section: Overall Complication Ratesmentioning
confidence: 91%
“…Such complications are rare in UAE as the patients are young with no underlying arterial disease and procedural anticoagulation with heparin is not required. Groin haematoma has been reported in 0.25-20 % of patients (Pinto et al 2003;Spies et al 2002;Manyonda et al 2011;Goodwin et al 2006;Siskin et al 2006;Dutton et al 2007), arterial injury has been seen in up to 0.5-10 % (Pinto et al 2003;Spies et al 2002;Pelage et al 2000), femoral nerve injury in up to 1.6 % (Razavi et al 2003;Spies et al 2002) and adverse reaction to contrast medium in up to 2.5 % (Spies et al 2002;Manyonda et al 2011;Dutton et al 2007). The majority of these complications are minor requiring either no secondary intervention or overnight stay for observation.…”
Section: Complications Of Angiographymentioning
confidence: 94%
“…Conflicting results regarding the effect of UAE on pregnancy and miscarriage rates have been reported [42,[44][45][46]. Unfortunately, the largest prospective randomized trial that compared UAE with myomectomy, did not report on fertility because ethical approval had been denied to study this outcome [42]. Thus, at present, UAE in women with a child wish should probably be reserved for women in whom myomectomy is not feasible according to gynaecological counselling or for research settings (Level 2A).…”
Section: Outcome and Effectivenessmentioning
confidence: 99%
“…UAE is associated with a shorter hospital stay and fewer major complications but a higher rate of reintervention (Level 1B) [42,43].…”
Section: Outcome and Effectivenessmentioning
confidence: 99%
“…Стоит отметить, что ЭМА рассматривается и как альтер-нативный метод хирургическому лечению. Между тем опубликованы данные I. Manyonda [15], где отмечается сравнимая эффективность лапароскопической МЭ и ЭМА, и если ЭМА сопряжена с меньшим процентом ос-ложнений, то при этом вероятность рецидива миомы мат-ки значимо выше. Помимо введения эмболов в сосуди-стое русло, при котором наступает необратимая окклю-зия, разработаны методы по созданию временной окклю-зии в бассейне маточной артерии непосредственно перед МЭ.…”
unclassified